Uji Potensi Antibakteri Ekstrak Rumput Laut (Eucheuma cottonii) Dalam Sediaan Gel Terhadap Bakteri Staphylococcus aureus Dan Staphylococcus epidermidis - Panggabean, Mayrissa Boru; Lidia, Prisca Deviani; Lidia, Kartini (Universitas Nusa Cendana, 2022)
Background: Incorrect medicine usage in treating acnes (acne vulgaris) may cause unwanted side effects. Teratogenic effects due to retinoid use in pregnancy and breastfeeding women as well as antibiotic resistance on account of irrational antibiotic use are a few of the effects that may emerge. Natural ingredients such as seaweeds (Eucheuma cottonii) formulated in topical form is an alternative to solve this problem. Objective: To ascertain seaweed extract (Eucheuma cottonii) antibacterial potency test in gel form on staphylococcus aureus and staphylococcus epidermidis bacteria. Method: This research is a true experimental research with posttest-only group design. Treatment groups are clindamycin gel positive control, sterile aquadest negative group, and seaweed infused extract group with 5%, 10%, 15%, and 20% concentrations with Staphylococcus aureus and Staphylococcus epidermidis bacteria as testing bacteria. Antibacterial testing method is done using disk diffusion method. Raw data is analyzed using Kruskal-Wallis statistical test. Result: The diameter of zone of inhibition of seaweed extract gel on Staphylococcus aureus bacteria on the 20% concentration (4,51 mm), 15% concentration (0,265 mm), 10% concentration (0,05 mm), and 5% concentration (0,22 mm) is categorized as weak antibacterial potential. The diameter of zone of inhibition of seaweed extract gel on Staphylococcus epidermidis bacteria on the 20% concentration (10,37 mm) is categorized as strong antibacterial potential, whereas 15% concentration (3,545 mm), 10% concentration (4,045 mm), and 5% concentration (0,725 mm) is categorized as weak antibacterial potential. Analysis shows that there are significant differences between treatment groups with p value < 0,05. Conclusion: Seaweed extract (Eucheuma cottonii) in gel form has an antibacterial potency towards Staphylococcus aureus and Staphylococcus epidermidis bacteria. Keywords: Seaweed, Antibacterial, Acne, Gel